Disiplin Kerja Aparatur Sipil Negara pada Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Malang - Rizki Dwi Cahyono; Niki Puspita Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The study aims to determine the condition of discipline and efforts to enforce discipline, such as discipline in work attendance, complying with all regulations in work procedures, obeying superiors, being aware of all work and having a sense of responsibility. The type of research applied in this study is an analysis using a descriptive method that relies on a qualitative approach. Data collection techniques are carried out through observation and interviews. For the research subjects interviewed for data collection, they are employees of the Malang Regency DPRD Secretariat. The data analysis technique used is the Miles & Huberman method, which involves data reduction, data presentation, and drawing conclusions. The results of the study show that work discipline is very important to support employee success. The purpose of the work needs to be in line with the plan, both in terms of discipline in work attendance, complying with regulations in work procedures, obeying superiors, being aware of all work and having a sense of responsibility. The work discipline of state civil servants at the Malang Regency DPRD Secretariat shows quite good results, although there are still some violations of work discipline that occur, therefore work discipline must still be improved.